2016
DOI: 10.1016/j.envres.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-range transported air pollution from vegetation fires on daily mortality and hospital admissions in the Helsinki metropolitan area, Finland

Abstract: Our research provides suggestive evidence for an association of exposure to long-range transported PM from vegetation fires with increased cardiovascular mortality, and to a lesser extent with increased hospital admissions due to respiratory causes. Hence, vegetation-fire originated air pollution may have adverse effects on public health over a distance of hundreds to thousands of kilometres from the fires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 46 publications
0
53
0
2
Order By: Relevance
“…Wildfire smoke contains a wide range of compounds known to be harmful to human health, including fine particulate matter (PM 2.5 ), acrolein, benzene, carbon monoxide, and polycyclic aromatic hydrocarbons [8,9]. Exposure to these toxic compounds is of concern near the source, and extending several hundred to thousands of kilometers away [10][11][12]. While it has been shown that the toxic compounds from wildfire smoke travel long distances from the source, potentially exposing thousands of individuals, the health effects associated with wildfire smoke exposure are just beginning to be understood [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wildfire smoke contains a wide range of compounds known to be harmful to human health, including fine particulate matter (PM 2.5 ), acrolein, benzene, carbon monoxide, and polycyclic aromatic hydrocarbons [8,9]. Exposure to these toxic compounds is of concern near the source, and extending several hundred to thousands of kilometers away [10][11][12]. While it has been shown that the toxic compounds from wildfire smoke travel long distances from the source, potentially exposing thousands of individuals, the health effects associated with wildfire smoke exposure are just beginning to be understood [13].…”
Section: Introductionmentioning
confidence: 99%
“…In Helsinki, the greater impact may also be explained by the synergistic effect of heat waves and air pollution. In fact, long-range transport of pollutants from forest fires have been shown to have an effect on health outcomes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent studies, both the local sources and the regional transport would affected the air quality of city [5][6] . Seventy-two-hour back trajectories were applied to understand the relationship between hourly PM 2.5 concentrations and transport pathway of the air masses in Panjin.…”
Section: Resultsmentioning
confidence: 99%